2018
DOI: 10.1007/s00428-018-2417-y
|View full text |Cite
|
Sign up to set email alerts
|

Small oral tongue cancers (≤ 4 cm in diameter) with clinically negative neck: from the 7th to the 8th edition of the American Joint Committee on Cancer

Abstract: One of the main changes in the 8th edition of the American Joint Committee on Cancer (AJCC) for staging of oral cancer is the inclusion of depth of invasion (DOI) in the T category. However, cancers in different oral subsites have variable behavior, with oral tongue squamous cell carcinoma (OTSCC) being the most aggressive one even at early stage. Thus, it is necessary to evaluate the performance of this new T category in homogenous cohort of early OTSCC. Therefore, we analyzed a large cohort of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Now, in the AJCC8, the superficial tumor is classified as T1, while the deep tumor (>10 mm) is classified as T3, although both have the same dimension of ≤2 cm. This remarkable change in the classification category of small OTSCC was noted in our recent study (6).…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Now, in the AJCC8, the superficial tumor is classified as T1, while the deep tumor (>10 mm) is classified as T3, although both have the same dimension of ≤2 cm. This remarkable change in the classification category of small OTSCC was noted in our recent study (6).…”
supporting
confidence: 56%
“…According to the evaluation with AJCC8, 25 cases were reclassified, and in particular, the use of ENE in pN classification identified patients with worse diseasefree survival and overall survival (P<0.05). We also recently re-classified our multicenter cohort of 311 early-stage cases (cT1-2N0, based on the 7th edition) according to the AJCC8, and compared the prognostic capacity of both systems (6). We noted that many cases were upstaged (even from cT1 to cT3) and were associated with worse diseasespecific survival and disease-free survival (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent work, in fact, Almangush et al reclassified 311 early-stage tongue SCC, suggesting a 2 mm DOI cut-off to upstage to T2 and a 4 mm threshold for upstaging to T3. According to their proposal, T3 disease had an even worse DSS, but the difference between T1 and T2N0 was still not significant (11).…”
Section: Validation?mentioning
confidence: 92%
“…By contrast, retrospective validation studies showed a similar DSS for T1 and T2N0 disease as identified by the last edition of the TNM staging system (4,10-12). This was another effect of the staging migration described above: since survival of T2N0 tongue SCC improved as more invasive cancers were clustered in Stage III disease, the existent gap between T1 and T2N0 scenarios was reduced in a parallel way (4,(10)(11)(12)17). At the same time, small cancers (<2 cm), infiltrating in depth more than 5 mm, migrated from T1 to T2.…”
Section: Validation?mentioning
confidence: 98%